Equilibrium and ultrafast kinetic studies manipulating electron transfer: A short-lived flavin semiquinone is not sufficient for electron bifurcation - Hoben, John P. (J Biol Chem, 2017)
Flavin-based electron transfer bifurcation is emerging as a fundamental and powerful mechanism for conservation and deployment of electrochemical energy in enzymatic systems. In this process, a pair of electrons is acquired at intermediate reduction potential (i.e. intermediate reducing power), and each electron is passed to a different acceptor, one with lower and the other with higher reducing power, leading to “bifurcation.” It is believed that a strongly reducing semiquinone species is essential for this process, and it is expected that this species should be kinetically short-lived. We now demonstrate that the presence of a short-lived anionic flavin semiquinone (ASQ) is not sufficient to infer the existence of bifurcating activity, although such a species may be necessary for the process. We have used transient absorption spectroscopy to compare the rates and mechanisms of decay of ASQ generated photochemically in bifurcating NADH-dependent ferredoxin-NADP(+) oxidoreductase and the non-bifurcating flavoproteins nitroreductase, NADH oxidase, and flavodoxin. We found that different mechanisms dominate ASQ decay in the different protein environments, producing lifetimes ranging over 2 orders of magnitude. Capacity for electron transfer among redox cofactors versus charge recombination with nearby donors can explain the range of ASQ lifetimes that we observe. Our results support a model wherein efficient electron propagation can explain the short lifetime of the ASQ of bifurcating NADH-dependent ferredoxin-NADP(+) oxidoreductase I and can be an indication of capacity for electron bifurcation.